1980
DOI: 10.3168/jds.s0022-0302(80)82938-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of Hydrogen Peroxide by Lactobacillus acidophilus

Abstract: Hydrogen peroxide production in reconstituted skim milk (10%) and low-fat milk by four strains lf Lactobacillus acidophilus was studied at 37 and 4 C. Strains A and B produced little, but strains C and D produced larger amounts, especially if agitated continuously during growth at 37 C or storage at 4 C. Continuous shaking was required at 4 C for C or D (4.0 X 10(8)/ml) to produce sufficient hydrogen peroxide to retard growth of Pseudomonas fragi. Flavin adenine dinucleotide stimulated the oxidation of reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 19 publications
3
48
2
4
Order By: Relevance
“…The beneficial effects of lactic acid bacteria has been attributed to their ability to suppress the growth of pathogens, probably by secretion of antibacterial substances such as lactic acid (Bhatia et al, 1989;Gibbe, 1987;Silva et al, 1987), peroxide (Collins and Aramalk, 1980), and bacteriocins (Barefood and Klaenhammer, 1983;McCormick and Savage, 1983). In the present study, we emphasized that strain DS-12 is super to some aspects for probiotics of aquiculture compared with the type strain of W. strain has high suppression against some pathogenic bacteria, in particular E. tarda, P. piscida, A. hydrophila, and V. anguillarum, using the differed assay method.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of lactic acid bacteria has been attributed to their ability to suppress the growth of pathogens, probably by secretion of antibacterial substances such as lactic acid (Bhatia et al, 1989;Gibbe, 1987;Silva et al, 1987), peroxide (Collins and Aramalk, 1980), and bacteriocins (Barefood and Klaenhammer, 1983;McCormick and Savage, 1983). In the present study, we emphasized that strain DS-12 is super to some aspects for probiotics of aquiculture compared with the type strain of W. strain has high suppression against some pathogenic bacteria, in particular E. tarda, P. piscida, A. hydrophila, and V. anguillarum, using the differed assay method.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of many psychotropic microorganisms and pathogens at refrigeration temperatures and also vaginal colonization by pathogenic species can be prevented using oral administration of different LABs with hydrogen peroxide production potential [Monteagudo-Mera et al, 2012]. It has been demonstrated that some strains of L. acidophilus from dairy origins were able to inhibit Pseudomonas species by producing 1.18 to 1.62 mmol/L of hydrogen peroxide in agitated cultures [Collins & Aramaki, 1980]. Moreover, foodborne pathogens such as E. coli O157:H7, Salmonella (Table 3).…”
Section: Hydrogen Peroxide Productionmentioning
confidence: 99%
“…The dominant inhibitory factor produced by lactobacilli at refrigerating temperatures was identified as hydrogen peroxide [11,[19][20][21]. In this study production of hydrogen peroxide by L. delbrueckii at 5°C storage were obtained.…”
Section: Hydrogen Peroxide Production By L Delbrueckii During Storagmentioning
confidence: 99%